Insulin suppresses transcriptional activity of yes-associated protein in insulin target cells - Sayedyahossein, Samar (Mol Biol Cell, 2020)
Yes-associated protein (YAP), the main transcriptional coactivator of the Hippo pathway, integrates multiple inputs from different signaling cascades. Evidence implicates YAP in the control of cellular nutrient and energy status, but the underlying mechanisms are not fully elucidated. Here we show that insulin modulates YAP transcriptional activity in classic insulin target cells, namely HepG2 and C2C12. Insulin increases YAP phosphorylation and significantly decreases YAP abundance in HepG2 cell nuclei. Proximity ligation assay analysis revealed a marked reduction in the interaction of YAP with TEA domain (TEAD) transcription factors in the nuclei of insulin-exposed cells. Consistent with these findings, insulin impaired both YAP/TEAD-mediated transcription and transcription of YAP target genes in HepG2 and C2C12 cells. Serum starvation abrogated the effect of insulin on YAP phosphorylation and YAP transcription. Both the expression of two gluconeogenesis genes, G6PC and PCK1, and the inhibitory effect of insulin on these genes were attenuated in YAP-deficient HepG2 cells. Our results identify insulin as a previously undescribed suppressor of YAP activity in insulin target cells and provide insight into cross-talk between the insulin and Hippo pathways.